Eurekas and euphorias : the Oxford book of scientific anecdotes / Walter Gratzer. - Gratzer, Walter (Oxford University Press, 2002)
From the death of Archimedes at the hands of an irritated Roman soldier to the concoction of a superconducting witch's brew at the very close of the 20th century, the stories in this book pour out, told with wit and relish by Walter Gratzer.